Digital Parenting: Strategi untuk Mencegah Kecenderungan Narsistik pada Anak Usia Dini - Mustika, Rina; Listiana, Aan; Rachmawati, Yeni (Institut Agama Islam Negeri Madura, 2025)
Parenting as a strategy to minimize narcissistic tendencies in young children due to exposure to digital technology is becoming an increasingly relevant topic in today's era. Using a literature review method, this study analyzes data from various academic literature published in recent years through several scientific reference sources such as Google Scholar and Scopus. Digital parenting is defined as the form of supervision, restriction, and guidance provided by parents in directing their children's digital activities. Narcissistic tendencies in children are often triggered by excessive use of gadgets or internet access, which can disrupt their psychological and social development. The results of analyses from various sources indicate that uncontrolled digital exposure has the potential to increase excessive social validation-seeking behavior, reduce empathy, and affect children's academic performance. Conversely, the implementation of digital parenting strategies such as active control, content monitoring, limiting device usage time, and direct supervision can mitigate these risks. This study also found that a balance between digital activities and real-world interactions, combined with creative and purposeful parenting patterns, is a key factor in preventing narcissistic behavior from an early age. In conclusion, consistent and collaborative digital parenting between parents and educators plays a crucial role in supporting children's healthy psychological, social, and academic development amid the rapid advancement of digital technology.